The Quality of Dory Fillets based on Water Soluble Protein, Color, and Myoglobin Concentration - Nurfajrin Nisa; Mala Nurilmala; Tati Nurhayati; Nurlisa Butet (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
Fillet of dory is very easy to be find in Indonesian market with various brand and produsen.Imported dory fillet is preferred by consumer so far because it has a white color compare than localfillets. Color is the important parameter that used by consumers to determine the quality of filet. Thisstudy was aimed to determine the quality of local and imported fillets, including protein profile usingSDS PAGE, color measurement, and myoglobin extractability. The results of water soluble protein profilesshowed dory fillet contained 13-15 bands. The redness value (a*) of local fillet (DN, DL, DM) was highercompared others. However, imported fillet (DI) had the highest if redness index (a/b). Imported fillet (DI)showed the lowest concentration of myoglobin compared other samples.